Hadith on Career Women: A Study of Takhrij, Contextual Explanation, and Maqashid Sharia - Sukriah Sihombing; Sulaiman Muhammad Amir; Husnel Anwar Matondang (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This study examines the Prophet's hadiths on career women through an integrated approach: hadith authentication (takhrij), contextual interpretation (syarah), and the objectives of Islamic law (maqashid syariah). The background of this study is the tension between the textual understanding of hadith on the role of women and the increasing participation of Muslim women in professional careers. Previous studies have examined this issue separately from the perspective of Islamic law, psychological-sociological, or exegesis, without integrating these three methods of hadith science. Using a qualitative, literature-based design, this study analyzes seven thematic hadiths from Sahih al-Bukhari, Sahih Muslim, and Sunan Ibn Majah, supported by scientific literature from 2019–2024. The findings show: (1) hadiths on permission to leave the house, congregational prayer, and economic activities including the narration of Zainab bint Jahsy RA who was praised by the Prophet for working as a tanner have a valid chain of narration and allow and even praise women's participation in the public sphere; (2) contextual analysis through the principle of reconciliation (al-jam'u wa al-tawfiq) broadens the scope of interpretation for Muslim career women; (3) maqashid analysis proves that career activities support the five main objectives of sharia (al-daruriyyat al-khams). The novelty of this research lies in the integration of the three methods, which has never been done before